Peningkatan Kesiapan Mahasiswa Dalam Menempuh Praktek Lapangan Melalui Peer Teaching Dengan Pendekatan Kooperatif Jigsaw - Sri Waluyanti; Djoko Santoso (Faculty of Engineering, Universitas Negeri Yogyakarta, 2015)
The purpose of the study is to improve the readiness of the students in performing Field Practice through peer teaching practice and Jigsaw cooperative learning approach. The approach of the study used classroom action research with the subject of the study were the students of bachelor program of Electronical Engineering who took video technique course. The study was done by the following steps, pre-action to balance the researcher’s perception and debriefing consisting designing lesson plan and micro teaching. The validity of the instruments of pedagogy competency was analyzed by item correlation, the result were, preparation r=0,73; implementation r=0,89 and evaluation r=0,97. The result of reliability testing for preparation was very reliable with r=0,89; implementation is very reliable with r=0,97 and implementation is less reliable with r=0,53. The result of the study showed that the students get a real picture of teacher’s responsibility through the exposure to the experiences of peer-tutoring, preparation, teaching practice, and evaluating the result of the study.The students’competence in preparation, teaching, and evaluating the result of study was improved cycle by cycle. The improvement in students’teaching skills was followed by improvement of the result of video technique learning outcomes.